Carotid to Femoral Pulse Wave Velocity Reflects the Extent of Coronary Artery Disease. Issue 9 (1st August 2014) - Hofmann, Britt; Riemer, Marcus; Erbs, Christian; Plehn, Alexander; Navarrete Santos, Alexander; Wienke, Andreas; Silber, Rolf‐Edgar; Simm, Andreas
<x xml:space="preserve">Abstract</x> Arterial stiffness is a well‐established risk factor for cardiovascular disease and mortality. Carotid to femoral pulse wave velocity (cfPWV) as a measure of arterial stiffness was obtained in 155 (47 women; 67.2±9.1 years, range 44–87 years) patients with detected coronary artery disease (CAD) scheduled for coronary artery bypass surgery. The authors set out to analyze how cfPWV in CAD patients correlates with reference values for healthy, normotensive volunteers and whether cfPWV values reflect the extent of CAD. cfPWV was measured with an oscillometric device. Mean cfPWV value of CAD patients was 9.3±1.9 m/s vs 7.7±1.1 m/s in healthy volunteers (P<.0001). In a multiple regression model, age (P<.0001), sex (P=.006), systolic arterial pressure (P=.04), mean arterial pressure (P=.04), and severity of CAD (P<.001) emerged as independent predictive markers for cfPWV in CAD patients. This study established reference values for cfPWV in CAD patients measured with an oscillometric device and confirmed the strong association between arterial stiffness and severity of CAD.